Exploring the Influence of Social Media Marketing on Brand Trust, Brand Image, and Brand Loyalty for Fore Coffee - Rachmat Ramadhani, Muh.; Ariyanti, Maya (Publisher Cv. Inara, 2024)
Indonesia's utilization of digital services such as mobile payments, paid digital content, online transportation, and food delivery has been amplified due to the rise in internet and smartphone usage. The digitalization of the food and beverage (F&B) industry has experienced significant growth since 2015, particularly accelerated by the COVID-19 pandemic. According to McKinsey's research conducted in 2020, there was a significant 34% surge in the number of individuals using food delivery services during the pandemic. Fore Coffee, a coffee startup established in 2018, employs digital marketing strategies to enhance sales and promote brand recognition. Fore Coffee has successfully pleased customers using social media and mobile applications. This study utilizes the concept of brand trust to investigate the impact of social media marketing on brand image and customer loyalty. Research utilizes PLS-SEM. A digital survey was distributed to a total of 301 individuals who are customers of Fore Coffee within the previous six-month period. Studies indicate that social media marketing has a positive and significant influence on brand trust, leading to a positive impact on brand image and customer loyalty. A well-executed digital marketing strategy has the potential to enhance brand trust, image, and loyalty Keywords: Brand Image; Brand Loyalty; Brand Trust; Social Media Marketing